Peran Teknologi Digital Dalam Industri Terhadap Produktivitas Dan Kesejahteraan Ekonomi Migas - Edy Soesanto; Citra Wahyuningrum; Sendy Dewanto (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2024)
Currently, digital technology needs to be considered in Oil and Gas (Oil and Gas) companies. The Indonesian government revealed that the digital economy is a national economic recovery. Therefore, all business sectors, including the oil and gas sector, need to pay attention to the important role of technology in stimulating business. Quoted from Bisnis.com, Coordinating Minister for Economic Affairs Airlangga Hartarto said that the oil and gas industry contributes investment of US$ 10 billion per year. This paper discusses the impact of technological innovation in the oil and gas industry on productivity and economic welfare. The literature review will outline recent developments in oil and gas technology. The data and methodology used cover a specific time period to understand the relationship between technological innovation and economic development. The results of this analysis provide an in-depth understanding of the contribution of technological innovation to economic growth and societal well-being, providing valuable insights for future policy making